Laboratory evaluation of the optical properties of two extended-depth-of-focus intraocular lenses - Chae, Sue Hey; Son, Hyeck Soo; Khoramnia, Ramin; Lee, Kyung Heon; Choi, Chul Y. (BMC ophthalmology, 2020)
To experimentally compare the optical performance of two different Extended-Depth-of-Focus (EDOF) intraocular lenses (IOLs) using a standardized optical bench set-up.
Gesehen am 26.03.2020